Phase II Study of Ipilimumab in Men With Metastatic Prostate Cancer With an Incomplete Response to Androgen Deprivation Therapy - Graff, Julie N.; Stein, Mark N.; Surana, Rishi; Al Rabadi, Luai; Liu, Eric; Fong, Lawrence; Bailey, Shawna; Latour, Emile; Newby, Timothy A.; Moran, Amy E.; Beer, Tomasz M. (Frontiers in Oncology, 2020)
Background: Phase 3 studies of immune checkpoint inhibitors have not shown a survival benefit in prostate cancer, but some patients have a profound anticancer response. Patients and Methods: We evaluated the efficacy of the CTLA-4 targeted agent, ipilimumab, in metastatic prostate cancer patients who had an incomplete biochemical response to initial androgen deprivation therapy (ADT) alone. Ten patients were enrolled, each treated with ipilimumab 10mg/kg (every 3 weeks for up to 4 doses) with maintenance ipilimumab every 12 weeks for non-progressing patients. The primary endpoint was proportion of patients with an undetectable PSA. The total sample size was 30 patients, but there was an interim analysis planned at 10 for futility. If none of the 10 patients achieved an undetectable PSA, the study would be halted. Results: The study was halted at the interim analysis as none of the 10 patients achieved the primary endpoint, but 30 percent of patients demonstrated a >50 percent reduction in PSA, with one patient achieving a >90 percent reduction in PSA. Peripheral blood mononuclear cells (PBMC) examined by mass cytometry showed that patients with clinical responses had an increase in effector memory T-cell subsets as well as an increase in T-cell expression of T-bet, suggesting induction of a Th1 response. Conclusions: This study provides further evidence that ipilimumab has activity in some patients with prostate cancer and provides further rationale for the development of future studies aimed at identifying a subset of patients with CPRC that are more likely to derive a benefit from treatment with ipilimumab.